Correlation between Troponin I and Serum Sodium and Potassium Levels in Acute Coronary Syndrome - Rahma, Hadiyatur; Loesnihari, Ricke; Siregar, Dewi Indah Sari (Indonesian Journal of Medicine, 2024)
Background: Acute Coronary Syndrome covers a spectrum of conditions that include patients who have recently changed symptoms or clinical signs, with or without changes in the 12-lead electrocardiogram, and with or without acute elevations in cardiac troponin (Tn) concentrations. Advances in technology have refined troponin testing and increased its accuracy in detecting and measuring cardiomyocyte injury, high sensitivity, and can detect small myocardial necrosis that is not detected on an electrocardiogram or CKMB examination. This study aims to analyze the correlation between troponin I and sodium and potassium levels in acute coronary syndrome. Subjects and Method: This study was an analytical observational research with a cross-sectional design, involving 40 patients with acute coronary syndrome who visited the Integrated Heart Center Emergency Department. The independent variable is acute coronary syndrome, while the dependent variables are troponin I, sodium, and potassium. The study was conducted at H.Adam Malik Hospital in Medan from February to March 2024. Patients were interviewed for medical history, and then blood samples were taken for troponin I examination and serum electrolyte (sodium and potassium) examination. Data were analyzed using the Spearman correlation test. Results: 40 study subjects, most of the study subjects over 55 years, mostly male (72.5%), with a smoking history of 67.5%, and a family history of hypertension of 52.5%. The median troponin I level was 6.09 ng/ml (range 0.12-15), the median sodium level was 143.5 mmol/L (range 130-155), and the mean potassium level was 4.19 mmol/L (SD= 0.52). There was a weak and non-significant positive correlation between troponin I and sodium (r= 0.129, p= 0.429), as well as a weak and non-significant positive correlation between troponin I and potassium (r= 0.059, p= 0.717). Conclusion: There was no correlation between troponin I and sodium, as well as troponin I and potassium.